THE POLICY INSTRUMENTS OF STREET VENDOR RELOCATION IN SURABAYA BULAK FISH CENTER - Nurany, Fierda (DIA: Jurnal Administrasi Publik, 2021)
The purpose of this study was to determine the policy instruments used by the Surabaya City Government to move street vendors to Bulak Fish Center. The background is because not all street vendors are ready to occupy the Bulak Fish Center. This study uses Howleet and Ramesh's theory to categorize policy instruments into three groups: Voluntary, Combined, and Compulsory Instruments. The research method used is descriptive qualitative with in-depth interviews. The research results reveal that the Surabaya City Government uses only five types of policy instruments. First, families and communities provide information to the community about the relocation of street vendors to Bulak Fish Center. Second, policies provide space to interact with street vendors, community leaders, and religious groups. Third, the policy of providing information and advice to all Surabaya local governments to keep Bulak Fish Center alive for a month. Fourth, the policy prohibiting selling in the old location. Fifth, the policy is to provide cleaning staff and transport vehicles directly to roadside vendors. However, 50 percent of the street vendors are still willing to occupy the Bulak Fish Center. Thus, the policy tools used by the Surabaya City Government have not been optimal, so that it has become a factor in the failure of roadside trade relocation operations.